Macroeconomic Determinants of Stock Market Development: A Systematic Literature Review - Akash Chaurasia; Prashant Debnath; Mohammed Juraij N (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this study is to examine the various macroeconomic factors that influence the growth of the stock market, as well as to explore the techniques employed to establish a correlation between them. For this research, literature was sourced from databases such as Ebsco host, Web of Science, and JSTOR using the search terms